The interface is on the table: Systematic Literature Review about interaction design to applications for tangible tabletops. - Da Costa, Vinicius Kruger; Zen, Eliana; Tavares, Tatiana Aires (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Tangible tabletops enable natural and social interaction, fostering collaborative applications that leverage human capabilities to manipulate physical objects. The potential use of tangible tabletops spans various fields of knowledge, and shared interfaces represent a growing trend. These devices find their place in interactive environments, where applications, once specific to particular uses, are becoming more generic and applicable to broader contexts. It is crucial to understand all elements involved in the interaction process on tangible tabletops and their impact on application design. In this way, this article presents a Systematic Literature Review (SLR) of scientific production over the past five years (starting 1256 articles) to delineate the state-of-the-art in tangible tabletops and their applications. By analyzing 53 articles, this review identifies interaction design challenges for applications that use this technology. The overall aim is to encourage discussion about developing applications that consider both the possibilities and limitations of tangible tabletops and to define essential elements for a future interaction design framework.